Education as a predictor of liver testing behaviour: Insights from a large-scale MASLD awareness survey in India - Kanica Kaushal; Manoj Kumar Sharma; Priyanka Aggarwal; Smriti Singh; Sumridhi Gautam; Anamika Tomar; Guresh Kumar; Siddhesh Mhatre (PLoS ONE, 2025)
Introduction Metabolic dysfunction-associated steatotic liver disease (MASLD) is a growing public health concern, yet awareness remains low. This study aimed to assess MASLD awareness and identify predictors of liver testing behavior in Jaipur, India. Methods A cross-sectional survey of 2,102 adults was conducted from October 2023 to March 2024. Participants completed a questionnaire assessing liver health knowledge, awareness, and testing history. Logistic regression analyzed predictors of liver testing. Results Only 5.9% of participants had heard of fatty liver disease, with 94.0% completely unaware. Knowledge of liver functions was extremely low, with only 14.9% recognizing food digestion as a liver function. The liver testing rate was 1.8% overall. Education emerged as the strongest predictor of testing behavior, with graduates and above 8.35 times more likely to be tested than non-graduates (OR=8.35, 95% CI: 3.80–18.37, p < 0.001). Participants with higher liver function knowledge had dramatically higher testing rates of 12.9% versus 1.2% for those with low knowledge (OR=9.35, 95% CI: 4.2–20.8, p < 0.001). Employment status also significantly predicted testing (OR=5.42, 95% CI: 2.8–10.5, p < 0.001). Discussion This study reveals a catastrophic knowledge deficit regarding MASLD, with 94% of participants completely unaware of the condition. The strong association between education, knowledge, and testing behavior highlights a critical knowledge-to-action pathway. The extremely low overall testing rate (1.8%) indicates massive underutilization of liver health screening, particularly among unemployed and less educated individuals. These findings underscore the urgent need for comprehensive public health education on liver health, especially given India’s rising MASLD prevalence and young demographic profile. Targeted interventions to improve awareness and facilitate testing access among socioeconomically disadvantaged groups are essential to address this public health crisis.